Plant palatability and trait responses to experimental warming - Dostálek, Tomáš; Rokaya, Maan Bahadur; Münzbergová, Zuzana (Scientific reports, 2020)
Climate warming is expected to significantly affect plant-herbivore interactions. Even though direct effects of temperature on herbivores were extensively studied, indirect effects of temperature (acting via changes in host plant quality) on herbivore performance have rarely been addressed. We conducted multiple-choice feeding experiments with generalist herbivore Schistocerca gregaria feeding on six species of genus Impatiens cultivated at three different temperatures in growth chambers and a common garden. We also studied changes in leaf morphology and chemistry. We tested effects of temperature on plant palatability and assessed whether the effects could be explained by changes in the leaf traits. The leaves of most Impatiens species experienced the highest herbivory when cultivated at the warmest temperature. Traits related to leaf morphology (specific leaf area, leaf dry matter content and leaf area), but not to leaf chemistry, partly mediated the effects of temperature on plant palatability. Herbivores preferred smaller leaves with lower specific leaf area and higher leaf dry matter content. Our study suggests that elevated temperature will lead to changes in leaf traits and increase their palatability. This might further enhance the levels of herbivory under the increased herbivore pressure, which is forecasted as a consequence of climate warming.
Keywords: Grasshoppers; Animals; Temperature; býložravci; kobylky; Climate Change; fenotyp; zvířata; Phenotype; Plant Leaves; teplota; Herbivory; listy rostlin; Impatiens; klimatické změny